Multiresponsive polyanionic microgels with inverse pH responsive behavior by encapsulation of polycationic nanogels. Issue 7 (6th November 2013) - Knipe, Jennifer M.; Chen, Frances; Peppas, Nicholas A.
ABSTRACT Intelligent, stimuli‐responsive hydrogels have great utility in various fields spanning biomedical technology, separations, and catalysis. Their overall response to surrounding fluids may be further tailored to a specific application by incorporation of one or more intelligent responses within one material, known as multiresponsive hydrogels. This is a report on the facile synthesis and characterization of poly(methacrylic acid‐co‐N‐vinylpyrrolidone) microgels encapsulating polycationic nanogels (70–100 nm) to incorporate inverse pH responsive behavior within a single hydrogel. Potentiometric titration and pH swelling studies reveal a swelling response dependent on both pH and crosslinking agent. Additionally, a protein and a small molecule are loaded and released to evaluate the pH‐dependent binding affinity. Such a material could exhibit unique protein‐binding capacity and pH‐responsive behavior for use in separation or drug delivery applications. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40098.